A method for producing clean gasoline
By using Ni/ZnO-Al2O3-graphene oxide-ZSM-5/β composite functional microspherical catalysts to perform hydrodesulfurization, olefin aromatization and isomerization reactions in the fluidized bed hydrogenation process, the problems of octane loss and poor olefin reduction effects in the prior art were solved, and deep desulfurization and olefin reduction effects that meet the national VI and above cleaning gasoline standards were achieved.
Patent Information
- Application Number
- CN202210012100.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-07
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-01-07
AI Technical Summary
The prior art is difficult to deeply desulfurize catalytically crack gasoline without losing its octane number, especially to reduce the olefin and aromatic content in gasoline while meeting the national VI and above cleaning gasoline standards.
The fluidized bed hydrogenation process is combined with Ni/ZnO-Al2O3-graphene oxide-ZSM-5/β composite functional microspherical catalyst, and the olefin content is deeply desulfurized and the olefin content is reduced through hydrodesulfurization, partial aromatization and isomerization reactions.
With basically no loss of octane, the sulfur content, olefin content and aromatic content in gasoline are significantly reduced, meeting the World Wide Fuel Charter Class V standard cleaning gasoline standards.
Smart Images

Figure CN116445184B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petroleum refining, and in particular relates to a method for producing clean gasoline. Background Art
[0002] Starting from 2019, China will implement the National VI clean vehicle gasoline standard (GB1793-2016) in stages, which will be implemented in two stages, A and B. The National VIA standard requires sulfur content ≯10µg / g, olefin content ≯18.0v%, and aromatic content ≯35.0v%. The National VIB standard further limits the olefin content to below 15.0v% and aromatic content ≯35.0v%. China is a major catalytic cracking country, and the gasoline components produced by catalytic cracking units account for about 80% of the total gasoline products in the country. The sulfur content in catalytic cracking gasoline is generally 200~1000µg / g, the olefin content is generally 20.0v%~45.0v%, and the aromatic content is generally 20.0v%~30.0v%. The sulfur and olefin contents in catalytic cracking gasoline are both high. How to further reduce the sulfur content and olefin content in catalytic cracking gasoline and then produce finished gasoline that meets the National VI and above clean gasoline standards is a difficult problem that oil refining companies urgently need to solve.
[0003] The main technologies for desulfurization of catalytic cracking gasoline are OCT-M series from Dalian Petrochemical Research Institute of Sinopec, Prime-G + Selective hydrodesulfurization process and S zorb adsorption desulfurization process are representative. The selective hydrodesulfurization process technology uses Mo-Co / Al2O3 as a hydrodesulfurization catalyst, and adopts the process of light and heavy gasoline fractionation and heavy fraction gasoline hydrodesulfurization. When producing clean gasoline with a sulfur content of ≯10µg / g, the octane number loss is large. When producing gasoline with a national VI standard of olefins ≯15.0v%, the hydrogenation saturation of olefins will cause the product octane number loss to increase further. S zorb technology uses NiO-ZnO as an adsorbent and uses an adsorption-regeneration cycle process to treat full-fraction catalytic cracking gasoline. Compared with the raw material, its product has a significantly reduced sulfur content, a slight reduction in olefins, a slight increase in alkanes, and a (RON+MON) / 2 loss of less than 1.0 unit. However, this method cannot significantly reduce the olefin content in gasoline products. For catalytic cracking gasoline with a high olefin content, it cannot solve the problem of reducing olefins.
[0004] CN100526430C discloses a method for producing clean gasoline. The method uses a modified ZSM-5 molecular sieve as a catalyst and adopts a fluidized bed process to hydrodesulfurize and aromatize low-quality FCC gasoline with high sulfur and high olefin content into clean gasoline with low sulfur and low olefin content. However, the disadvantage of this method is that in order to meet the restriction that the total aromatic content of clean gasoline for vehicles is not more than 35.0v%, the aromatization rate is low, and the aromatic content is generally increased from about 22.0v% to 31.5v%.
[0005] In the existing desulfurization technology for inferior gasoline, the aromatization reaction of gasoline components is mainly to reduce the octane loss caused by olefin saturation. Its disadvantages are that on the one hand, the aromatization rate of the existing technology is low due to the restriction of aromatic content in the clean gasoline standard; on the other hand, the small amount of heavy aromatics produced by the aromatization reaction easily makes the product fraction heavier and the dry point increased, which cannot meet the requirement of distillation dry point ≯205℃ in the clean gasoline standard. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for producing clean gasoline. The method can convert low-quality gasoline into clean gasoline products by deep desulfurization without losing octane number, meeting the standards of Class V clean gasoline of the World Wide Fuel Charter: sulfur content ≯10.0µg / g, olefins ≯10.0%, aromatics ≯35.0%, benzene content ≯0.8v%, and distillation dry point ≯205℃.
[0007] The production method of clean gasoline of the present invention comprises the following contents: inferior gasoline raw material and hydrogen enter into a fluidized bed reactor, and hydrodesulfurization, olefin partial aromatization and isomerization reaction are carried out on a Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microsphere catalyst to obtain a desulfurized and reduced olefin product.
[0008] In the method of the present invention, the inferior gasoline raw material and hydrogen enter from the lower part of the fluidized bed reactor, contact with the catalyst entering the reactor, and perform desulfurization, partial aromatization of olefins and isomerization reaction in a fluidized bed state, and the reaction product is discharged from the top of the reactor; the catalyst discharged from the lower part of the reactor and deactivated by sulfur and carbon deposition enters the regenerator through a lock hopper, is regenerated by burning sulfur and carbon with air, and the sulfur-containing flue gas is discharged to recover sulfur; the regenerated catalyst enters the reactor through a lock hopper and is recycled.
[0009] In the method of the present invention, the distillation range of the inferior gasoline raw material is 35-205° C., and the raw material is selected from one or more of catalytic cracking (FCC) gasoline, catalytic deep cracking (DCC) gasoline and coking gasoline, wherein the sulfur content is generally 100-800 μg / g, the volume content of olefins is 15.0v%-40.0v%, and the volume content of aromatics is 20.0v%-30v%.
[0010] In the method of the present invention, the operating conditions in the fluidized bed reactor are as follows: reaction pressure of 1.0-4.0 MPa, reaction temperature of 350-550°C, volume space velocity of 2.0-6.0 h -1 , hydrogen to oil volume ratio 10:1 to 100:1; the preferred operating conditions are as follows: reaction pressure 1.5 to 2.5 MPa, reaction temperature 400 to 500 ° C, volume space velocity 3.0 to 5.0 h -1 , hydrogen-oil volume ratio 30:1~50:1.
[0011] In the method of the present invention, the catalyst to be regenerated discharged from the reactor is transported to the regenerator for regeneration after gas stripping, and the obtained regenerated catalyst is returned to the fluidized bed reactor for recycling. The regeneration conditions are as follows: pressure of 0.5MPa to 1.5MPa, gas-to-agent volume ratio of 200:1 to 500:1, calcination at 400 to 500°C for 0.2 to 1.0 hours, and the regeneration atmosphere is an oxygen-containing atmosphere, preferably air.
[0012] In the method of the present invention, the Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microspherical catalyst, the carrier is a ZSM-5 / β composite molecular sieve with graphene oxide on the surface, and a zinc oxide and aluminum oxide composite spherical carrier. Based on the mass of the carrier, the ZSM-5 / β composite molecular sieve with graphene oxide on the surface is 30.0%~80.0%, preferably 50.0%~70.0%; the zinc oxide is 20.0%~60.0%, preferably 30.0%~50.0%; the balance is aluminum oxide; the active metal component is one or more of Ni, Mo or W, preferably Ni; based on the weight of the catalyst, the content of the active metal component in terms of oxide is 5.0wt%~20.0wt%, preferably 8.0wt%~15.0wt%.
[0013] The specific surface area of the catalyst of the present invention is 300-450m 2 / g, pore volume 0.55~0.65cm 3 / g.
[0014] The ZSM-5 / β composite molecular sieve with graphene oxide on the surface of the present invention has a graphene oxide content of 0.1wt% to 10.0wt% and a ZSM-5 / β composite molecular sieve content of 90.0wt% to 99.9wt% based on the weight of the ZSM-5 / β composite molecular sieve with graphene oxide on the surface. Preferably, the graphene oxide content is 0.5wt% to 8.0wt% and the ZSM-5 / β composite molecular sieve content is 92.0wt% to 99.5wt%; wherein the particle size of the nano ZSM-5 / β composite molecular sieve with graphene oxide on the surface is 10 to 100nm.
[0015] The composite functional microsphere desulfurization catalyst described in the method of the present invention is prepared by a spray drying molding method, including but not limited to the following steps: ZSM-5 molecular sieve with graphene oxide on the surface, zinc oxide and aluminum oxide are mixed and ground evenly, a nitric acid aqueous solution containing the metal component Ni is added to form a slurry, and the slurry is spray dried and calcined to prepare the composite functional microsphere desulfurization catalyst.
[0016] The specific but not limited preparation method of the composite functional microsphere catalyst of the present invention includes the following contents:
[0017] a) mixing and grinding a ZSM-5 molecular sieve with graphene oxide on its surface, zinc oxide and aluminum oxide, kneading and extruding, drying and calcining to obtain a strip-shaped carrier; wherein the strip-shaped carrier is dried at 100 to 200° C. for 3 to 6 hours and calcined at 400 to 600° C. for 3 to 6 hours;
[0018] b) crushing the strip carrier obtained in step a), and then sieving it, and the sifted powder is used for later use; the sieving process can be carried out by selecting different mesh sieves according to actual needs. Generally, the mesh number can be selected from 100 to 400;
[0019] c) adding the powder obtained in step b) into an aqueous nitric acid solution containing a metal component Ni to form a slurry;
[0020] d) The slurry obtained in step c) is spray-formed and then calcined to obtain a catalyst.
[0021] Wherein, the solid-liquid mass ratio of the slurry is 0.25~0.65g / mL, preferably, 0.3~0.5g / mL.
[0022] The spray drying molding process is carried out in a spray drying device, such as a spray drying tower. The hot air inlet pressure of the spray drying device is 3.0-7.0 MPa, the inlet temperature is 300-400°C, and the outlet temperature is 120-200°C. The microspheres obtained by the cyclone separator are calcined at 400-600°C for 3.0-10.0 hours.
[0023] The composite functional microsphere catalyst has a particle diameter of 10 to 80 μm, and in particular, microspheres with a diameter of 30 to 60 μm account for 60 wt% to 95 wt% of the total particles, preferably 80 wt% to 95 wt%.
[0024] The method for preparing the ZSM-5 / β composite molecular sieve with graphene oxide on the surface described in the method of the present invention comprises the following specific steps:
[0025] 1) Mix silicon source, aluminum source, template (TPAOH aqueous solution) and deionized water in a certain proportion to form a ZSM-5 synthesis system (Solution A);
[0026] 2) Mix the silicon source, aluminum source, template (tetraethylammonium hydroxide) and deionized water in a certain proportion to form a β synthesis system (solution B);
[0027] 3) After crystallizing solution A at 90-150°C for 3-24h, centrifuge to obtain ZSM-5 nanoparticles, disperse the ZSM-5 particles in the β synthesis system (solution B), and stir for 1-30 minutes to form a homogeneous slurry;
[0028] 4) The homogeneous slurry obtained in step 3) is formed into particles by a spray drying device, and the solid powder obtained by drying is crystallized in three stages, which are crystallization at 80-120° C. for 3 h to 24 h, crystallization at 180-220° C. for 1 h to 12 h, and crystallization at 130-180° C. for 8 h to 72 h. The product is washed, filtered, dried, and calcined to remove the template agent to obtain the final ZSM-5 / β composite molecular sieve product;
[0029] 5) Mixing graphene oxide and ZSM-5 / β composite molecular sieve, subjecting to a first microwave treatment, adding an alkaline solution for a second microwave treatment, filtering, and drying to obtain a ZSM-5 / β composite molecular sieve with graphene oxide on the surface.
[0030] The solution A is characterized in that the amount of each reaction raw material added is such that the molar ratio of each component in the system is: A12O3: SiO2: tetrapropylammonium hydroxide: water = 1: 20-200: 3-10: 500-1000.
[0031] The B solution is characterized in that the amount of each reaction raw material added is such that the molar ratio of each component in the system is: A12O3: SiO2: tetraethylammonium hydroxide: water = 1: 20-200: 1-20: 500-1000.
[0032] The silicon source is one or more of tetraethyl orthosilicate, silica sol, and water glass; the aluminum source is one or more of aluminum sulfate, aluminum chloride, aluminum isopropoxide, and sodium aluminate.
[0033] The amount of ZSM-5 particles added is 25-75% of the final ZSM-5 / β composite molecular sieve output.
[0034] The conditions of the first microwave treatment are as follows: microwave power is 500-900 W, and the treatment time is 0.5-3.0 h. The conditions of the second microwave treatment are as follows: microwave power is 500-800 W, and the treatment time is 1.0-4.0 h.
[0035] The alkaline solution may be potassium hydroxide and / or sodium hydroxide aqueous solution, and the mass percentage concentration of the alkaline solution is 5.0% to 40.0%. The solid-liquid volume ratio of step 5) is 1.5:1 to 2.5:1.
[0036] Compared with the prior art, the method of the present invention has the following characteristics:
[0037] The present invention adopts a fluidized bed hydrogenation process and cooperates with the Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microsphere catalyst of the present invention. The gasoline raw material first undergoes a desulfurization reaction in which sulfides such as mercaptans, thiophene, and alkylthiophene are converted into H2S at the Ni hydrogenation desulfurization center on the catalyst surface, and then H2S is adsorbed to the ZnO active center; and olefins also undergo reactions such as olefin isomerization to isoolefins, olefin aromatization to aromatics, and benzene alkylation to alkylbenzene on the active center of the ZSM-5 / β composite molecular sieve covered with graphene oxide on the surface. The synergistic effect of olefin isomerization and aromatization, on the one hand, compensates for the octane number loss caused by olefin hydrogenation saturation, and on the other hand, reduces the degree of aromatization, limits the increase of the aromatic content and benzene content of the gasoline product, and does not lead to an increase in the dry point of the gasoline.
[0038] The Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microsphere catalyst of the present invention first combines the carrier components by extrusion, and forms carrier pores during drying and calcination, so that the carrier simultaneously obtains high mechanical strength and anti-wear performance; secondly, the carrier is crushed and sieved to obtain a number of micrometer-sized reaction unit particles that retain the original pores and specific surface properties, which are equivalent to a plurality of micrometer-sized reaction unit precursors; and thirdly, the plurality of micrometer-sized reaction unit particles are immersed in an active metal solution, so that the active metal is fully dispersed on the micrometer-sized reaction unit particles and dispersed more evenly on the carrier, which greatly improves the dispersion of the active centers on the microsphere-shaped desulfurization catalyst, increases the contact area between the reaction raw materials and the active centers, and accelerates the reaction rate. At the same time, the catalyst of this particle size is more conducive to increasing the diffusion rate of reactants and products inside and outside the catalyst in a fluidized bed reaction system, and can achieve hydrodesulfurization at a higher space velocity, reduce the residence time, and achieve the multifunctional effects of hydrodesulfurization, olefin aromatization and isomerization reactions. Description of the drawings
[0039] Figure 1 The figure is a schematic flow chart of a method for producing clean gasoline according to the present invention.
[0040] Figure 2 This is the pore size distribution diagram of the microsphere catalyst in Comparative Example 1.
[0041] Figure 3 This is the pore size distribution diagram of the microsphere catalyst in Comparative Example 2.
[0042] Figure 4 This is the pore size distribution diagram of the microsphere catalyst in Example 1.
[0043] Figure 5 This is the scanning electron microscope (SEM) image of the microsphere catalyst in Comparative Example 1.
[0044] Figure 6 This is the scanning electron microscope (SEM) image of the microsphere catalyst in Comparative Example 2.
[0045] Figure 7 This is a scanning electron microscope (SEM) image of the microsphere catalyst in Example 1.
[0046] Figure 8 This is a scanning electron microscope (SEM) image of the microsphere catalyst in Example 2.
[0047] Fig. 9 This is a scanning electron microscope (SEM) image of the microsphere catalyst in Example 2. DETAILED DESCRIPTION
[0048] The method and effects of the present invention are further described below in conjunction with the accompanying drawings and examples, but the scope of protection of the present invention is not limited thereby. In the present invention, the specific surface area and pore volume are measured by low temperature liquid nitrogen adsorption BET method.
[0049] according to Figure 1 Schematic diagram of the process: low-quality gasoline raw material 1 and hydrogen 2 enter the riser 3 from the bottom and are lifted into the fluidized bed reactor 4, where hydrodesulfurization, olefin aromatization and isomerization reactions are carried out under certain conditions; the reaction product 12 is discharged from the top of the reactor 4. The deactivated catalyst with sulfur and carbon deposition enters the catalyst collector 5 to be regenerated, and after the hydrogen is replaced by nitrogen 7, it enters the lock hopper 6, enters the regenerator 9, and is regenerated by burning sulfur and carbon with an oxygen-containing atmosphere (such as air) 10, and the sulfur-containing flue gas 11 is discharged to recover sulfur; the regenerated catalyst enters the regenerated catalyst collector 8, enters the lock hopper 6 through a pipeline, and enters the riser 3 through a pipeline for recycling.
[0050] The scheme and effect of the present invention are further illustrated by the following examples, but the present invention is not limited thereto.
[0051] Comparative Example 1
[0052] Comparative Example: Preparation of 10.0wt% NiO / ZnO-Al2O3-ZSM-5 microsphere catalyst.
[0053] Weigh 80g dry nano ZSM-5 molecular sieve (SiO2 / Al2O3 molar ratio of 70), 80.0g dry ZnO and 20.0g dry Al2O3 powder, grind and mix evenly, add 300mL of 10g / 100mL dilute nitric acid solution and deionized water to prepare 600mL slurry. The above slurry is spray dried, the spray drying pressure is 3.0MPa, the drying tower inlet temperature is 350℃, and the outlet temperature is 150℃. The microspheres obtained by the cyclone separator are calcined at 550℃ for 5 hours to prepare microsphere carriers.
[0054] Weigh 90g of the above microsphere carrier and put it into the spray tank, start the rotary pump. Spray 63.0mL of nickel nitrate solution containing 10.0g NiO into the catalyst carrier within 30 minutes. After drying at room temperature, dry at 120℃ for 6 hours and calcine at 500℃ for 4 hours to prepare a microsphere catalyst, which is numbered as RZ-1 catalyst.
[0055] The physical properties of RZ-1 catalyst are listed in Table 1. Figure 2 This is the pore size distribution diagram of RZ-1 catalyst. Figure 5 This is the TEM image of RZ-1 catalyst.
[0056] Comparative Example 2
[0057] In this comparative example, a 10.0wt% NiO / ZnO-Al2O3-ZSM-5-β molecular sieve microsphere catalyst was prepared.
[0058] Weigh 56g dry nano ZSM-5 molecular sieve (SiO2 / Al2O3 molar ratio of 70), 24g dry β molecular sieve (SiO2 / Al2O3 molar ratio of 70), 80.0g dry ZnO powder and 20.0g dry Al2O3 powder, grind and mix evenly, add 300mL of 10g / 100mL dilute nitric acid solution and deionized water to prepare 600mL slurry. The above slurry is spray dried, the spray drying pressure is 3.0MPa, the drying tower inlet temperature is 350℃, and the outlet temperature is 150℃. The microspheres obtained by the cyclone separator are calcined at 550℃ for 5 hours to prepare microsphere carriers.
[0059] Weigh 90g of the above microsphere carrier and put it into the spray tank, start the rotary pump. Spray 63.0mL of nickel nitrate solution containing 10.0g NiO into the catalyst carrier within 30 minutes. After drying at room temperature, dry at 120℃ for 6 hours and calcine at 500℃ for 4 hours to prepare a microsphere catalyst, which is numbered as RZ-2 catalyst.
[0060] The physical properties of RZ-2 catalyst are listed in Table 1. Figure 3 This is the pore size distribution diagram of RZ-2 catalyst. Figure 6 This is the TEM image of RZ-2 catalyst.
[0061] Example 1
[0062] In this example, a 10.0 wt% NiO / ZnO-Al2O3-surface-coated graphene oxide ZSM-5 / β molecular sieve microsphere catalyst was prepared.
[0063] 0.75g sodium aluminate, 30g silica sol (30wt% silica aqueous solution), 24.36g tetrapropylammonium hydroxide (25% aqueous solution), and 47g deionized water were stirred and mixed to form a uniform precursor solution A. Then it was transferred to a polytetrafluoroethylene-lined reactor and sealed, and statically crystallized at 110°C for 12 hours. After washing and filtering, ZSM-5 particles were obtained. 1.5g sodium aluminate, 60g silica sol, 35g tetraethylammonium hydroxide (25% aqueous solution), and 79g deionized water were stirred and mixed to form a uniform precursor solution B. The obtained ZSM-5 particles were evenly dispersed in the B solution and stirred for 30 minutes to form a uniform mixed solution. The liquid is converted into spray through a spray drying device, and the solid powder obtained after drying is crystallized at 90°C for 4h, 200°C for 3h, and 170°C for 48h. The product is washed, filtered, dried, and calcined to remove the template to obtain the final ZSM-5 / β composite molecular sieve product.
[0064] Weigh 0.5 g of graphene oxide (GO) and 60 g of ZSM-5 / β composite molecular sieve and add them to a beaker, put them into a microwave and treat them at 700 W for 1.0 h, then add 94 mL of 10 wt % potassium hydroxide solution and continue to treat them at 600 W for 2.0 h, take out and filter, and dry at 120 ° C for 8.0 h to obtain a ZSM-5 / β composite molecular sieve with graphene oxide on the surface.
[0065] Weigh 56g of ZSM-5 / β composite molecular sieve with graphene oxide on the dry surface, 80.0g of ZnO powder on the dry basis and 20.0g of Al2O3 powder on the dry basis, grind and mix them evenly, add 300mL of 10g / 100mL dilute nitric acid solution and deionized water to prepare 600mL of slurry. The slurry is spray dried at a spray drying pressure of 3.0MPa, a drying tower inlet temperature of 350℃, and an outlet temperature of 150℃. The microspheres obtained by the cyclone separator are calcined at 550℃ for 5 hours to prepare microsphere carriers.
[0066] Weigh 90g of the above microsphere carrier and put it into the spray tank, start the rotary pump. Spray 63.0mL of nickel nitrate solution containing 10.0g NiO into the catalyst carrier within 30 minutes. After drying at room temperature, dry at 120℃ for 6 hours and calcine at 500℃ for 4 hours to prepare a microsphere catalyst, which is numbered as NZ-1 catalyst.
[0067] The physical properties of NZ-1 catalyst are listed in Table 1. Figure 4 This is the pore size distribution diagram of NZ-1 catalyst. Figure 7 TEM image of NZ-1 catalyst.
[0068] Example 2
[0069] In this example, a 15.0wt% NiO / ZnO-Al2O3-surface-coated graphene oxide ZSM-5 / β molecular sieve microsphere catalyst was prepared.
[0070] The preparation method of ZSM-5 / β molecular sieve coated with graphene oxide is shown in Example 1.
[0071] Weigh 96g of ZSM-5 / β molecular sieve with graphene oxide on the surface, 54.0g of dry basis ZnO and 20.0g of dry basis Al2O3 powder, grind and mix evenly, add 300mL of dilute nitric acid solution with a concentration of 10g / 100mL and deionized water to prepare 340mL of slurry. The above slurry is spray dried, the spray drying pressure is 3.0MPa, the drying tower inlet temperature is 350℃, and the outlet temperature is 150℃. The microspheres obtained by the cyclone separator are calcined at 520℃ for 8 hours to prepare microsphere carriers.
[0072] Weigh 85g of the above microsphere carrier and put it into the spray tank, and start the rotary pump. Spray 65.0mL of nickel nitrate solution containing 15.0g NiO into the catalyst carrier within 30 minutes. After drying at room temperature, dry at 120℃ for 6 hours, and calcine at 480℃ for 6 hours to prepare a microsphere catalyst, which is numbered as NZ-2 catalyst. The physical properties of NZ-2 catalyst are listed in Table 1. Figure 5 This is the scanning electron microscope (SEM) image of NZ-2 catalyst. Figure 8 TEM image of NZ-2 catalyst.
[0073] Example 3
[0074] In this example, a 15.0wt% NiO / ZnO-Al2O3-surface-coated graphene oxide ZSM-5 / β molecular sieve microsphere catalyst was prepared.
[0075] The preparation method of ZSM-5 / β molecular sieve coated with graphene oxide is shown in Example 1.
[0076] Preparation of strip carrier: Weigh 96g of dry-basis nano ZSM-5 molecular sieve, 54.0g of dry-basis ZnO, 20.0g of dry-basis Al2O3 powder and 10g of sesbania powder extrusion aid, mix and roll to mix. Then add 50mL of 10% nitric acid solution, mix and roll to mix into a plastic powder, use an extruder to prepare cylindrical strips with a diameter of 1.5mm, dry at 120℃ for 8 hours, and calcine at 520℃ for 5 hours to prepare a strip carrier;
[0077] Preparation of microsphere catalyst: Grind the prepared strip carrier and pass it through a 100-200 mesh sieve to obtain a powder. Take 18g of nickel nitrate hexahydrate and add 40mL of deionized water to prepare a solution. Take 50g of the sieved powder and add it to the solution. Ultrasonic dispersion is carried out at an ultrasonic frequency of 50Hz for 30 minutes to form a peptized slurry. The obtained slurry is spray dried using a laboratory small spray dryer. The spray drying pressure is 6.0MPa, the inlet temperature is 280℃, and the outlet temperature is about 150℃. The microspheres obtained by spray drying are directly calcined at 450℃ for 5 hours to prepare a microsphere catalyst; it is numbered as NZ-3 catalyst. The physical properties of NZ-3 catalyst are listed in Table 1. Fig. 9 This is the scanning electron microscope (SEM) image of NZ-3 catalyst.
[0078] Comparative Example 3
[0079] This comparative example examines the performance of the catalyst in Comparative Example 1.
[0080] 20 mL of new RZ-1 catalyst was loaded into Figure 1 In the fluidized bed reactor, hydrogen was introduced to increase the pressure. The new RZ-1 catalyst was reduced for 4 hours at a hydrogen pressure of 1.2 MPa, a temperature of 400°C, and a hydrogen agent volume ratio of 20:1. Then, the new RZ-1 catalyst was reduced at a volume space velocity of 3.0 h -1 The FCC gasoline feedstock was fed into the reactor at a hydrogen-oil volume ratio of 20:1 for desulfurization and aromatization reaction; the hydrodesulfurization product was sampled and analyzed. Table 2 lists the results of the FCC gasoline feedstock and hydrogenation product.
[0081] Comparative Example 4
[0082] This comparative example examines the performance of the catalyst in Comparative Example 1.
[0083] 20 mL of new RZ-2 catalyst was loaded into Figure 1 In the fluidized bed reactor, hydrogen was introduced to increase the pressure. The new RZ-1 catalyst was reduced for 4 hours at a hydrogen pressure of 1.2 MPa, a temperature of 400°C, and a hydrogen agent volume ratio of 20:1. Then, the new RZ-1 catalyst was reduced at a volume space velocity of 3.0 h -1 The FCC gasoline feedstock was fed into the reactor at a hydrogen-oil volume ratio of 20:1 for desulfurization, aromatization, and isomerization reactions; the hydrodesulfurization products were sampled and analyzed. Table 3 lists the results of the FCC gasoline feedstock and hydrogenation products.
[0084] Example 4
[0085] This example examines the performance of the catalyst in Example 1.
[0086] 20 mL of new NZ-1 catalyst was loaded into Figure 1 In the fluidized bed reactor, hydrogen was introduced to increase the pressure. The new NZ-1 catalyst was reduced for 4 hours at a hydrogen pressure of 2.0 MPa, a temperature of 430°C, and a hydrogen agent volume ratio of 50:1. Then, the volume space velocity was 5.0 h -1 , hydrogen-to-oil volume ratio of 50:1, and FCC gasoline feedstock was added for desulfurization, aromatization, and isomerization reactions; Table 4 lists the results of FCC gasoline feedstock and hydrogenation products.
[0087] Example 5
[0088] This example examines the performance of the catalyst in Example 2.
[0089] 20 mL of new NZ-2 catalyst was loaded into Figure 1 In the fluidized bed reactor, hydrogen was introduced to increase the pressure. The new LZ-1 catalyst was reduced for 4 hours at a hydrogen pressure of 1.6 MPa, a temperature of 450°C, and a hydrogen-to-agent volume ratio of 20:1. Then, the volume space velocity was 7.0 h -1 , hydrogen-to-oil volume ratio of 20:1, and FCC gasoline feedstock was added for desulfurization, aromatization, and isomerization reactions; Table 5 lists the results of FCC gasoline feedstock and hydrogenation products.
[0090] Example 6
[0091] This example examines the performance of the catalyst in Example 3.
[0092] 20 mL of new NZ-3 catalyst was loaded into Figure 1 In the fluidized bed reactor, hydrogen was introduced to increase the pressure. The new LZ-1 catalyst was reduced for 4 hours at a hydrogen pressure of 1.6 MPa, a temperature of 430°C, and a hydrogen-to-agent volume ratio of 20:1. Then, the volume space velocity was 7.0 h -1 , hydrogen-to-oil volume ratio of 20:1, and FCC gasoline feedstock was added for desulfurization, aromatization, and isomerization reactions; Table 6 lists the results of FCC gasoline feedstock and hydrogenation products.
[0093] Table 1 Catalyst properties
[0094]
[0095] Table 2 Properties of FCC gasoline feedstock and product in Comparative Example 3
[0096]
[0097] Table 3 FCC gasoline feedstock and product properties in Comparative Example 4
[0098]
[0099] Table 4 Properties of FCC gasoline feedstock and product in Example 4
[0100]
[0101] Table 5 FCC gasoline feedstock and product properties in Example 5
[0102]
[0103] Table 6 FCC gasoline feedstock and product properties in Example 6
[0104]
[0105] From the comparison of Tables 2 to 6, we can see that a low-quality FCC gasoline feedstock with a sulfur content of 242µg / g, an olefin content of 35.0%, an aromatic content of 25.0%, and a distillation dry point of 200°C:
[0106] 1) After hydrogenation desulfurization and aromatization of olefin reduction by RZ-1 catalyst of Comparative Example 1, the sulfur content of hydrogenation product was 7.4µg / g, olefin content was 10.4%, aromatic content was 30.4%, and RON loss was 1.6 units. However, especially the distillation range dry point was increased to 220℃, which could not meet the index requirement of clean gasoline distillation range dry point ≯205℃.
[0107] 2) After hydrogenation desulfurization, aromatization, isomerization and olefin reduction by RZ-2 catalyst of Comparative Example 2, the sulfur content of hydrogenation product was 7.3μg / g, olefin content was 9.5%, aromatic content was 28.2%, and RON loss was 1.0 unit. However, especially the distillation range dry point was increased to 210℃, which could not meet the index requirement of clean gasoline distillation range dry point ≯205℃.
[0108] 3) After hydrodesulfurization, aromatization and isomerization to reduce olefins using the NZ-1 catalyst of Example 1, the hydrogenation product has a sulfur content of 7.1 µg / g, an olefin content of 9.6%, an aromatics content of 25.7%, a RON loss of 0.1 units, and a distillation dry point of 203°C; therefore, the requirement of a clean gasoline distillation dry point ≯205°C can be met.
[0109] 4) After hydrodesulfurization and aromatization to reduce olefins using the NZ-2 catalyst of Example 2, the hydrogenation product has a sulfur content of 5.2 µg / g, an olefin content of 6.1%, an aromatics content of 25.9%, a distillation range dry point of 202°C, and a RON increase of 0.2 units; therefore, the clean gasoline distillation range dry point ≯205°C index requirement can be met.
[0110] 5) After hydrodesulfurization and aromatization to reduce olefins using the NZ-3 catalyst of Example 3, the hydrogenated product has a sulfur content of 2.2 µg / g, an olefin content of 3.1%, an aromatics content of 25.5%, a distillation range dry point of 200°C, and a RON increase of 0.6 units; therefore, the clean gasoline distillation range dry point ≯205°C index requirement can be met.
Claims
1. A method for producing clean gasoline, characterized in that The invention comprises the following contents: inferior gasoline raw materials and hydrogen enter a fluidized bed reactor, and carry out hydrodesulfurization, partial aromatization of olefins and isomerization reaction on a Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microsphere catalyst to obtain a desulfurized and reduced olefin product; the operating conditions in the fluidized bed reactor are as follows: reaction pressure of 1.0-4.0MPa, reaction temperature of 350-550℃, volume space velocity of 2.0-6.0h -1 , hydrogen-oil volume ratio of 10:1 to 100:1; the Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microspherical catalyst, the carrier is a ZSM-5 / β composite molecular sieve with graphene oxide on the surface, a zinc oxide and an aluminum oxide composite spherical carrier, based on the carrier mass, the ZSM-5 / β composite molecular sieve with graphene oxide on the surface is 30.0%~80.0%, the zinc oxide is 20.0%~60.0%, and the balance is aluminum oxide; the active metal component is Ni; based on the weight of the catalyst, the content of the active metal component in terms of oxide is 5.0wt%~20.0wt%; based on the ZSM- The invention discloses a method for preparing a Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microspherical catalyst, which is based on the weight of the ZSM-5 / β composite molecular sieve, the content of graphene oxide is 0.1wt%~10.0wt%, and the content of ZSM-5 / β composite molecular sieve is 90.0wt%~99.9wt%; the particle size of the ZSM-5 / β composite molecular sieve coated with graphene oxide on the surface is 10~100nm; the preparation method of the Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microspherical catalyst comprises the following contents: the ZSM-5 molecular sieve coated with graphene oxide on the surface, zinc oxide and aluminum oxide are mixed and evenly ground, a nitric acid aqueous solution containing the metal component Ni is added to form a slurry, and the slurry is spray-dried, formed and calcined to prepare the microspherical catalyst.
2. The production method according to claim 1, characterized in that: The inferior gasoline raw material and hydrogen enter from the lower part of the fluidized bed reactor, contact with the catalyst entering the reactor, and perform desulfurization, partial aromatization of olefins, and isomerization reactions in a fluidized bed state, and the reaction product is discharged from the top of the reactor; the catalyst deactivated by sulfur and carbon deposition discharged from the lower part of the reactor enters the regenerator through a closed hopper, is regenerated by burning sulfur and carbon with air, and the sulfur-containing flue gas is discharged to recover sulfur; the regenerated catalyst enters the reactor through a closed hopper and is recycled.
3. The production method according to claim 1 or 2, characterized in that: The distillation range of the inferior gasoline raw material is 35-205° C., wherein the sulfur content is 100-800 μg / g, the volume content of olefins is 15.0 v%-40.0 v%, and the volume content of aromatics is 20.0 v%-30 v%.
4. The production method according to claim 1 or 2, characterized in that: The inferior gasoline raw material is selected from one or more of catalytic cracking gasoline, catalytic deep pyrolysis gasoline and coking gasoline.
5. The production method according to claim 1 or 2, characterized in that: The operating conditions in the fluidized bed reactor are as follows: reaction pressure of 1.5-2.5 MPa, reaction temperature of 400-500°C, volume space velocity of 3.0-5.0 h -1 , hydrogen-oil volume ratio 30:1~50:
1.
6. The production method according to claim 2, characterized in that: The regeneration conditions are as follows: pressure of 0.5MPa to 1.5MPa, gas-to-agent volume ratio of 200:1 to 500:1, calcination at 400 to 500°C for 0.2 to 1.0 hour, and the regeneration atmosphere is an oxygen-containing atmosphere.
7. The production method according to claim 1, characterized in that: The preparation method of the Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microsphere catalyst comprises the following contents: a) mixing and grinding a ZSM-5 molecular sieve with graphene oxide on the surface, zinc oxide and aluminum oxide, kneading and extruding, drying and calcining to obtain a strip-shaped carrier; wherein the strip-shaped carrier is dried at a temperature of 100-200°C for 3-6 hours and calcined at a temperature of 400-600°C for 3-6 hours; b) crushing the strip-shaped carrier obtained in step a), and then sieving it, and the sieved powder is reserved; c) adding the powder obtained in step b) to a nitric acid aqueous solution containing a metal component Ni to form a slurry; d) spraying and molding the slurry obtained in step c), and then calcining it to obtain a catalyst; wherein the solid-liquid mass ratio of the slurry is 0.25-0.65 g / mL.
8. The production method according to claim 1 or 7, characterized in that: The spray drying molding process is carried out in a spray drying device, the hot air inlet pressure of the spray drying device is 3.0-7.0MPa, the inlet temperature is 300-400°C, and the outlet temperature is 120-200°C; the microspheres obtained by the cyclone separator are calcined at 400-600°C for 3.0-10.0 hours.
9. The production method according to claim 1 or 7, characterized in that: The Ni / ZnO-Al2O3-graphene oxide-ZSM-5 / β composite functional microsphere catalyst has a particle diameter of 10 to 80 μm, of which microspheres with a diameter of 30 to 60 μm account for 60 wt% to 95 wt%.
10. The production method according to claim 1 or 7, characterized in that: The preparation method of ZSM-5 / β composite molecular sieve with graphene oxide on the surface comprises the following specific steps: 1) Solution A: silicon source, aluminum source, tetrapropylammonium hydroxide and deionized water are mixed uniformly in a certain proportion to form a ZSM-5 synthesis system; 2) Solution B: silicon source, aluminum source, tetraethylammonium hydroxide and deionized water are mixed uniformly in a certain proportion; 3) Solution A is crystallized at 90-150° C. for 3-24 hours, and then centrifuged to obtain ZSM-5 nanoparticles, and the ZSM-5 particles are dispersed in solution B, and stirred for 1-30 minutes to form a homogeneous slurry; 4) the homogeneous slurry obtained in step 3) is formed into particles by a spray drying device, and the solid powder obtained by drying is crystallized in three stages, which are crystallized at 80-120° C. for 3 hours to 24 hours, Crystallize at 180-220°C for 1h-12h, and at 130-180°C for 8h-72h. The product is washed, filtered, dried, and calcined to remove the template agent, thereby obtaining the final ZSM-5 / β composite molecular sieve product. 5) The graphene oxide and the ZSM-5 / β composite molecular sieve are mixed, subjected to a first microwave treatment, and then an alkaline solution is added for a second microwave treatment, and the mixture is filtered and dried to obtain a ZSM-5 / β composite molecular sieve with graphene oxide on the surface.
11. The production method according to claim 10, characterized in that: In the solution A, the molar ratio of the reaction raw materials is: A12O3: SiO2: tetrapropylammonium hydroxide: water = 1: 20-200: 3-10: 500-1000.
12. The production method according to claim 10, characterized in that: In the solution B, the molar ratio of the reaction raw materials is: A12O3: SiO2: tetraethylammonium hydroxide: water = 1: 20-200: 1-20: 500-1000.
13. The production method according to claim 10, characterized in that: The silicon source is one or more of tetraethyl orthosilicate, silica sol or water glass; the aluminum source is one or more of aluminum sulfate, aluminum chloride, aluminum isopropoxide or sodium aluminate.
14. The production method according to claim 10, characterized in that: The added amount of the ZSM-5 particles is 25%-75% of the final output of the ZSM-5 / β composite molecular sieve with graphene oxide on the surface.
15. The production method according to claim 10, characterized in that: The conditions of the first microwave treatment are as follows: microwave power is 500-900 W, and the treatment time is 0.5-3.0 h; the conditions of the second microwave treatment are as follows: microwave power is 500-800 W, and the treatment time is 1.0-4.0 h.
16. The production method according to claim 10, characterized in that: The alkaline solution is potassium hydroxide and / or sodium hydroxide aqueous solution, and the mass percentage concentration of the alkaline solution is 5.0% to 40.0%; the solid-liquid volume ratio of the step 5) is 1.5:1 to 2.5:1.
Citation Information
Patent Citations
Production process of producing cleaning gasoline
CN100526430C
Graphene / molecular sieve / metal oxide composite catalyst and preparation method thereof
CN106475132A
Method for producing super clean gasoline
CN106701177A